Risk factors for stroke in the African populace: need for action - Paul Bolaji (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2024)
The burden of stroke cannot be overemphasized especially in low and middle-income countries (LMICs). More than two-thirds of stroke deaths arise from these countries as well as nearly 90% of stroke-related morbidities. Unfortunately, it has been suggested that there might be up to a three-fold increase in stroke incidence and a higher prevalence in Africa in the year 2021. The known risk factors for stroke are similar to those in developed countries: age, hypertension, diabetes mellitus, hypercholesterolaemia, and central obesity. These risk factors have often been overlooked in patients who present with stroke in Africa. Other important risk factors for stroke include high salt intake and red meat consumption, low consumption of green leafy vegetables, air pollution, undernutrition in infancy and genetic factors. Possibly the most efficient way of curbing the impact of stroke in Africa is to address the risk factors. The aim of this article is to shine some light on these risk factors in sub-Saharan Africa and proffer some solutions to address the menace of stroke.